The Role of The Civil Judge in Assessing and Outweighing the Testimony - Bakhtyar Sabir Baiz; Chiya Ismaail Salih (QALAAI ZANIST JOURNAL, 2021)
Although the testimony is issued under the influence of oath and it is usually assumed that the witness has no interest in what he testifies, the possibility that the testimony is far from truthfulness is possible, and therefore the testimony is considered within restricted and non-binding proof of evidence for the judge. From here comes the positive role of the judge in assessing the testimony from both the objective and personal aspects and his outweighs for testimony from one of the parties to the other in case of inconsistency between them, and this in order to reach the truth and prevent injustice, because fraud testimony is a cause of injustice and tyranny, and it is considered a major lesion that stands in the way of justice.